Exploring the water mite fauna (Acari, Hydrachnidia) of the Madeira archipelago: DNA Barcoding reveals a remarkable species endemicity - Pešić, Vladimir; Zawal, Andrzej; Bankowska, Aleksandra; Araújo, Ricardo; Sługocki, Łukasz; Rewicz, Tomasz; Krakowiak, Maja; Michoński, Grzegorz; Girão, Dinis; Silva, Luis P. Da; Órfão, Inês; Raposeiro, Pedro M.; et al. (Zootaxa, 2025)
Water mites represent the group with the highest degree of endemism among all macroinvertebrates living in freshwater habitats of Madeira. The water mite fauna of this archipelago has been well known for a long time, but until now they have not been molecularly investigated. So far, 25 species of water mites have been recorded, most of them endemic to Madeira. The library presented here covers 584 COI DNA barcodes grouped into 23 Barcode Index Numbers (BINs), which represent the genetic barcodes of 23 species (more than 80% of the known Madeira water mite fauna). Our study shows that COI barcode clusters generated by the Barcode of Life Data Systems (BOLD) matches to morphological identifications of specimens, with one exception in the family Lebertiidae. A large-scale comparison of the new sequences with those available in public databases such as BOLD confirmed the uniqueness of the genetic diversity of water mites inhabiting Madeira. Neumania atlantida Lundblad, 1941, a species previously synonymized with N. uncinata Walter, 1927, is resurrected as a valid species. Additionally, genetic data revealed that Sperchon brevirostris Koenike, 1895, a species common in freshwaters of Europe and Macaronesia, consists of multiple genetic lineages, one of which is restricted to Madeira. Finally, our research revealed three species new to the water mite fauna of Madeira, i.e., Hydrachna skorikowi Piersig, 1900, Arrenurus bicuspidator Berlese, 1885 and Lebertia algeriensis Lundblad, 1942. The latter species, found to be common in the running waters of the island, may be the first species of water mite documented as potentially, if not invasive, then non-indigenous in freshwater ecosystems of Madeira.